The value of preseason screening for injury prediction: The development and internal validation of a multivariable prognostic model to predict indirect muscle injury risk in elite football (soccer) players - Hughes, T.; Riley, R: D.; Callaghan, M. J.; Sergeant, J. C. (Sports Medicine - Open, 2020)
Background In elite football (soccer), periodic health examination (PHE) could provide prognostic factors to predict injury risk.